Reconceptualizing Franchisee Performance: A Configurational Approach in a Base‐of‐the‐Pyramid Context - Newbery, Robert; McKague, Kevin; Muñoz, Pablo; Kimmitt, Jonathan (British journal of management, 2025)
This paper proposes and tests a new conceptual framing for franchisee performance that draws on institutional complexity to explore the interaction of corporate, market, and relational logics of performance. Extant research draws on corporate and market logics to explain performance; however, this does not explain individual franchisee performance in complex institutional environments such as Base‐of‐the‐Pyramid (BoP) markets where relational logics may be more important, thereby limiting explanations of how franchisee outlets perform. Drawing on data from a network of 58 franchise outlets in the context of Kenya, we conduct a configurational analysis related to sales outcomes. We leverage fuzzy‐set qualitative comparative analysis (fsQCA) to map out the conditions under which franchisees exhibit higher sales performance. Results show that three distinct configurations can lead to increased sales performance. Our results paint a nuanced picture of combinations of factors that result in franchisee success with relevance to the BoP context and beyond.